What Attracts Indonesians to Travel? A Study of Indonesian Tourist Destination Attributes - Immanuel Yosua; Christiany Suwartono (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
Indonesia is an archipelagic nation with natural beauty and diverse world‑class tourist destinations. The tourism sector has experienced rapid growth post‑pandemic, although it still leans toward well‑established destinations. Therefore, identifying destination attributes is crucial for understanding the attributes considered important by Indonesian tourist. This study used a quantitative design, enriched with a qualitative approach. Data were collected from 332 respondents through convenience sampling. It further utilized the Destination Attributes associated with Tourists’ Revisit Intention instrument modified for the Indonesian context. Data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. The results reveal that, quantitatively, the most important attribute for Indonesian tourists is the ambience of tourist attractions, followed by other attributes. This finding aligns with the qualitative insights, which highlight the significance of safety and comfort at destinations. Regarding tourism type, nature‑themed attributes are deemed most important and should be enhanced with supporting facilities and local hospitality. Nevertheless, this study has limitations because the participants were urban, young, and highly educated, limiting generalizability beyond this group. The study finally underscores the need for government and tourist managers to incorporate these findings to ensure the sustainability of tourism destinations.